(untitled) (Global Journal of Management and Business Research, 2016)
The case study is about Corporate Governance and its failure in India. We consider the corporate governance to be the main element when we have to talk about the success of a company but at the same time if it fails due to different reasons such as, the financial, social and political reasons, the consequences can be very serious. In order to understand the importance of this system we have tried to explain and define the notion of corporate governance being inspired by the studies already made in this field. In the second part of the paper we pointed out the benefits that a company enjoys when good corporate governance practices are embraced. In the third part we highlighted the principles and the models of corporate governance. In the fourth part of the paper we focused out attention on some resounding financial scandals from all over the world and then analyzed the causes that led to failures. Towards the end, we took a close look at the failure in corporate governance and tried to analyse the reasons that lead to failure.